Board strategic balance: an emerging sport governance theory - Ferkins, L.; Shilbury, D. (Sport Management Review, 2015)
Despite the important role governing boards play in organisational life our understanding of their strategic function is limited. This paper embarks on theory development to explain the notion of board strategic capability and to identify the factors and their relationships influencing strategic capability of sport boards. This little-used construct, we argue, can guide future governance research. In reflecting on the extant literature from the nonprofit, for-profit and sport governance domains, we derived six distinct and central factors of board strategic capability: increasing contribution of volunteer board members (`will and skill`); board operational knowledge; board integrating regional entities into the governing role; board maintaining the monitoring and control function; board co-leading strategy development; and board co-leading integration of strategy into board processes. In considering the relationships between these six factors, we propose a theory of `board strategic balance` that explains these influences in a holistic model. We conclude that the theory of board strategic capability is encapsulated by understanding how creating and maintaining equilibrium in these roles and functions is managed by sport boards.